Variabel-Variabel yang Mempengaruhi Perilaku Belanja Online Mahasiswa - Rosiana Agussetyaningsih (Jurnal Ekonomi dan Bisnis Digital, 2024)
In the current era of globalization, many conveniences are provided, including information technology, such as in the shopping process that can be done through the internet or better known as online shopping. This activity causes many problems, one of which is a person's consumptive behavior due to opening the marketplace too often and being fun with the ease of online shopping transactions and increasingly diverse payment methods, this consumptive activity can have an impact on student finances. This study was conducted using a quantitative method of multiple linear regression to find out whether the factors of benefit, risk, hedonistic motivation, psychology and site design have an effect on students' online shopping behavior. However, from the results of the analysis that has been carried out, statements from respondents show that the consumptive activities carried out are still in the category of reasonable, not excessive and do not interfere with their finances. So it can be concluded from the analysis that has been carried out shows that with ease of online shopping transactions, students are still able to regulate shopping behavior according to their economic abilities and the results of the analysis show that several factors studied have a significant influence on student spending behavior, especially students of the Faculty of Social and Political Sciences, National Development University "Veteran" East Java.